External rotor gearless elevator machine: a new design with flanged shaft - Soyaslan, Mucahit; Eldogan, Osman; Fenercioglu, Ahmet; Avsar, Yusuf (Springer Science and Business Media B.V., 2024)
The design of an external rotor gearless elevator machine (ERGEM) with a flanged shaft for elevator traction systems is presented in this paper. The machine is designed with two distinct shafts. The fixed shaft with stator is one, and the flanged shaft turns with the rotor is the other. The ERGEM's rotational movement has been reduced to a flanged shaft, and a novel motor design has been obtained that fits the market's traction pulleys and brake mechanisms. The flanged shaft provides traction by rotating with the pulley. Instead of making grooves on the rotor surface, an external pulley is used. The loads on the pulley have a negligible effect on the rotor because it is located between two fixing plates. With the plates on the right and left sides of the pulley, a symmetrical load distribution has been achieved. Finite element analyses (FEA) were performed using the maximum static load values. After the final design was approved, the prototype was built and experimental tests were conducted. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2023.
Keywords: Elevator systems; Elevator traction machine; External rotor; Gearless motor; Permanent magnet synchronous motors; Traction machine